2019
DOI: 10.1108/ijdi-10-2018-0156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exposure to mass media on female empowerment: evidence from India

Abstract: Purpose The purpose of this paper is to investigate if women’s exposure to mass media, i.e. television, radio, and print media, is a determinant of female empowerment in India. Indicators of empowerment include female autonomy in domestic decision-making, freedom of movement, financial knowledge and independence, attitudes regarding acceptability of violence against women, actual and desired fertility and use and decisions about contraception. Design/methodology/approach Data for the analysis come from two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
(71 reference statements)
4
17
0
Order By: Relevance
“…For example, it leads to reduction in fertility. Hence, policymakers, especially those in low and middleincome countries, are beginning to pay particular attention to issues relating to women empowerment, which includes their household decision-making capacity (Upadhyay et al, 2014;Prata et al, 2017;Dasgupta, 2019). Generally, women's empowerment concerns women's aptitude to have access to various aspects of development, including "health, education, earning opportunities, rights, and political participation" (Duflo, 2012), and their capability in making free choices (Torp, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, it leads to reduction in fertility. Hence, policymakers, especially those in low and middleincome countries, are beginning to pay particular attention to issues relating to women empowerment, which includes their household decision-making capacity (Upadhyay et al, 2014;Prata et al, 2017;Dasgupta, 2019). Generally, women's empowerment concerns women's aptitude to have access to various aspects of development, including "health, education, earning opportunities, rights, and political participation" (Duflo, 2012), and their capability in making free choices (Torp, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have revealed that mass media influences women empowerment, including their ability to take household decisions (Jensen and Oster, 2009;Ting et al, 2014;Dasgupta, 2019). However, such studies have largely, often focused on telenovelas and radio programs and their influence on women's child-naming practices (La Ferrara et al, 2012), use of prenatal services (Ghosh, 2006), and participation in social groups (Olken, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Bleck and Michelitch (2018) found that women's empowerment is positively associated with rural women's political knowledge and opinions in Mali. In a recent study, Dasgupta (2019) found favorable impact of exposure to mass media on female empowerment using household survey data.…”
Section: Literature Reviewmentioning
confidence: 99%